STATE SOVEREIGNTY OVER MINERAL RESOURCES IN FOREIGN INVESTMENT REGULATION AT MINING SECTOR IN INDONESIA - Lanini, Agus (Tadulako University, 2016)
Abstract State sovereignty over mineral resources such asan authority Â to manageÂ policy over mineral resouces, making regulation, and it implementation as mandatory of article 33 (3) UUDNRI 1945. Legal certainty and the honor toward international law as the basis of foreign investment agreement on mineral extraction between investment and the government of Indonesia that are established,Â would be still recognized until the end of its period. Due to the sovereignty implementation over mineral resources still faced various problems that the government as constitution mandatory should be clearly thorough establish an authority as government representative and responsible in making a legal transaction to the investor in the frame of full security guaranty investation. Keywords: Indonesia, Mineral, Sovereignty